Case Reports of Left Atrial Myxoma in Elderly and Children - Laksono, Sidhi; Surya, Steven Philip; Manuputty, Ferel; Lasanudin, Hengkie Frankie; Prawara, Ananta Siddhi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Cardiac myxoma is a rare heart disease. Cardiac myxoma can manifest in both intracardiac and extracardiac. This report describes the importance of a careful history taking, physical examination, echocardiography, and complete surgical resection for the management of atrial myxoma in two patients.Case Reports: We reported two cases: a 64 years old female and a 16 years old male with neurological deficit as the chief complaint. The two patients underwent brain imaging and echocardiography evaluation. Both were diagnosed with left atrial myxoma and brain infarction. Surgical resection of the left atrial myxoma was successfully done in both patients and afterward, both were being monitored in the outpatient clinic. During follow up, a gradual clinical improvement can be seen in the right extremities. Echocardiography examination was conducted at 1 month, 3 months, and 6 months follow-ups for both patients and no abnormalities were found. Discussion: Atrial myxomas are the most common primary cardiac tumors. Systemic embolization in atrial myxoma is uncommon manifest as neurological deficit with reported incidence around 20-35%. On the other hand, in stroke or transient ischemic attack patients, atrial myxoma were found in 1 out of 250 young adults and 1 out of 750 older patients. Transthoracic echocardiography (TTE) has up to 95% sensitivity on diagnosing atrial myxoma. The long-term prognosis of the patients when diagnosed and managed correctly is very good and surgery is curative with recurrence rate 1-3%. The patients in our case reports showed gradual clinical improvement with no sign of myxoma recurrence during follow up.Conclusion: Stroke is one of the extracardiac manifestations of atrial myxoma. Thus, it is crucial to evaluate the presence of atrial myxoma in stroke patients. The use of TTE is important in diagnosing atrial myxoma. Resection of atrial myxomas is curative with excellent long-term prognosis and low chance of recurrences.